Evolution of the structural and microstructural characteristics of SrSn1 - xTixO3 thin films under the influence of the composition, the substrate and the deposition method - Menezes de Oliveira, Andre Luiz; Bouquet, Valerie; Dorcet, Vincent; Ivier, Sophie; Deputier, Stephanie; Souza, Antonio Gouveia de; Siu-Li, Maximo; Longo, Elson [UNESP]; Weber, Ingrid Tavora; Garcia dos Santos, Ieda Maria; Guilloux-Viry, Maryline (Elsevier B.V., 2017)
SrSn1 (-) xTixO3 thin films were grown on R-sapphire and (100) LaAlO3 single crystal substrates by two different routes: chemical solution deposition (CSD) and pulsed laser deposition (PLD). Structural and microstructural characteristics of the films were determined by X-ray diffraction (theta-2 theta, omega-and -scans) and field emission scanning electron microscopy. Pure perovskite phase was obtained for all of the compositions, whatever the method of deposition and the substrate nature. On R-sapphire, a randomly oriented growth (polycrystalline) was observed for all of the compositions deposited by CSD while (h00) preferential orientation was attained when deposition was done by PLD, in particular for SrTiO3 composition. The phi-scan performed on this sample revealed that the (100) oriented grains present an in-plane ordering (epitaxial growth) with respect to the substrate with an alignment of the [011] direction of the film along the [121] direction of the substrate, explained on the basis of misfit considerations and interface arrangements. All of the films grown on (100) LaAlO3 exhibited an epitaxial growth with an in-plane relationship (010)(film)//(010)substrate As for the thin film microstructure, porosity, homogeneity, shape and size of the grains were strongly influenced by Ti content in the SrSn1 (-) (x)TixO(3) solid solution, and also by the nature of the substrate and by the deposition method. Moreover, the influence of the composition and thin film growth on the photoluminescence of SST films were also evaluated. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Thin films; Epitaxial growth; Surface/interface characteristics; Chemical solution deposition (CSD); Pulsed laser deposition (PLD); Photoluminescence